Vascular endothelial growth factor, hypoxia-inducible factor 1 alpha and CD34 expressions in early-stage gastric tumors: Relationship with pathological factors and prognostic impact on survival - ÇELİKEL, ÇİĞDEM; DANE, FAYSAL; YUMUK, PERRAN FULDEN (KARGER, 2007)
Background: Angiogenesis is one of the key steps in solid tumor growth and metastasis. We planned to investigate the prognostic significance of vascular endothelial growth factor (VEGF), hypoxia-inducible factor 1 alpha (HIF-1 alpha) and CD34 expressions as markers of angiogenesis in gastric cancer. Patients and Methods: We retrospectively reviewed the medical records of 51 gastric cancer patients who had total or subtotal gastrectomy at Marmara University Hospital from 1990 to 2004 and evaluated the expression of VEGF, HIF-1 alpha and CD34 by immunohistochemistry in their archival tumor tissues. We recorded the clinical and pathological characteristics of these patients and analyzed their survival outcome. Results: Thirty out of 51 patients were males. The median age was 63 years (range 34-81). The median follow-up was 17 months. Thirty-six patients had node-positive disease. The majority of patients (n = 43) had T2 and T3 disease. Vascular and lymphatic invasions were present in 57 and 77% of tumors, respectively. VEGF and HIF-1 alpha were positive in 65 and 71% of tumors. The median CD34 staining score was 19 (3-68). VEGF, HIF-1 alpha and CD34 expressions were more frequent in tumors without serosal invasion (p = 0.01, p = 0.01 and p = 0.003, respectively). CD34 expression was significantly more frequent in tumors with VEGF and HIF-1 alpha expression (p = 0.00, p = 0.00). HIF-1 alpha expression was more frequent in tumors with VEGF expression (p = 0.00). The 5year overall survival was 45%. VEGF, HIF-1 alpha, CD34 expressions and other pathological characteristics were found to have no impact on survival. Conclusion: VEGF, HIF-1 alpha and CD34 expressions were more common in tumors without serosal invasion. As a future perspective, biological agents targeting VEGF and HIF-1 alpha might be more effective at earlier stages of gastric cancer. Copyright (c) 2007 S. Karger AG, Basel.
Keywords: vascular endothelial growth factor; hypoxia-inducible factor 1 alpha; CD34; angiogenesis; gastric cancer; NITRIC-OXIDE SYNTHASE; FACTOR-C; MICROVASCULAR DENSITY; CLINICAL-SIGNIFICANCE; VEGF-C; CARCINOMA; CANCER; ANGIOGENESIS; OVEREXPRESSION; METASTASIS